Financial Literacy and Fintech Adoption in Indonesia: A Review from Campus Surveys and National Case Studies - Adrian Adrian; Oktavia Marpaung; Verdi Yasin; Samuel Horas Sarjana (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
The financial technology (fintech) sector in Indonesia has experienced significant growth with widespread adoption across various demographic groups. However, this development also reveals systemic vulnerabilities, particularly in the context of the financial literacy gap among users. This article explores the relationship between financial literacy and fintech adoption in Indonesia by integrating findings from campus surveys and national financial literacy reports. The study emphasises the importance of structured, integrated, and behaviour-change-focused national financial literacy programs. The article also offers strategic recommendations for integrating financial education into formal curricula, fostering cross-sector collaboration, and promoting ethical design on fintech platforms to safeguard users and promote digital financial inclusion. Keywords: Financial Literacy, Fintech Adoption, Education